The equation of this graph is  y = 23x − 4 What transformation would need to happen for the equation of the line to be y = 23x ?(1 point)ResponsesShift the graph down 3 and left 2Shift the graph down 3 and left 2Shift the graph up 4Shift the graph up 4Shift the graph left 4Shift the graph left 4Shift the graph right 3, down 2

1 answer

To transform the equation \( y = 23x - 4 \) to \( y = 23x \), you need to eliminate the \(-4\) term.

This involves shifting the graph upward by \(4\) units.

Therefore, the correct transformation is:

Shift the graph up 4.